Case Report: Pansynostosis, Chiari I Malformation and Syringomyelia in a Child With Frontometaphyseal Dysplasia 1 - Kim, Jaewon; Lee, Dong-Woo; Jang, Dae-Hyun (Frontiers in Pediatrics, 2021)
Abstract Frontometaphyseal dysplasia 1 (FMD1) is a rare otopalatodigital spectrum disorder (OPDSD) that is inherited as an X-linked trait and it is caused by gain-of-function mutations in the FLNA. It is characterized by generalized skeletal dysplasia, and craniofacial abnormalities including facial dysmorphism (supraorbital hyperostosis, hypertelorism, and down-slanting palpebral fissures). The involvement of the central nervous system in patients with OPDSD is rare. Herein, we present the case of a 12-year-old boy with facial dysmorphism, multiple joint contractures, sensorineural hearing loss, scoliosis, craniosynostosis, and irregular sclerosis with hyperostosis of the skull. Brain and whole-spine magnetic resonance imaging revealed Chiari I malformation with extensive hydrosyringomyelia from the C1 to T12 levels. Targeted next-generation sequencing identified a hemizygous pathologic variant (c.3557C>T/p.Ser1186Leu) in the FLNA, confirming the diagnosis of FMD1. This is the first report of a rare case of OPDSD with pansynostosis and Chiari I malformation accompanied by extensive syringomyelia.